Tengkulak dalam Sistem Ekonomi Petani Hortikultura Etnis Tengger Brang Wetan - Idris, Mohamad Fahmi; ., Aliffiati; Suarsana, I Nyoman (Sunari Penjor : Journal of Anthropology, 2022)
Middlemen or intermediaries are viewed negatively in society, especially in the farmer’s economic system. The role of the middleman is not always negative, the middleman also has a positive side. Middlemen or vagetable collectros who are present in the midst of the tengger Brang Wetan farming community in Argosari Village, senduro, Lumajang Regency. Farmers who are producitve, but have better business instincts than other farmars. Middlemen who have been present in agricultural life are sometimes considered to have a negative connotation the emphasis of this research methodolgy is on the use of qualitative methods and the analysis focuses on interpretive descriptive, the relationship betweeen farmers and middlemen begins with tading namely the relationship between sellers and buyers where the position of sellers and buyer between farmers and middlemen can be exchanged depending on the time and circumstances and needs between the two parties.